2005
DOI: 10.1080/03079450500179327
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxicosis, infectious bursal disease and immune response to Newcastle disease vaccination in rural chickens

Abstract: To investigate the immunosuppressive effects of infectious bursal disease virus (IBDV) and aflatoxin in indigenous chickens of Uganda, Newcastle disease (ND) seronegative chicks were randomly allocated to two treatment groups. Group A chicks were injected intramuscularly at the age of 3 weeks every 2 days up to four times with 0.250 mg aflatoxin B1 per bird, group B was infected occulo-nasally with IBDV 3 days prior to vaccination, while group C was left as a control group. All the chicks from the three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…It also modifies lipid metabolism and the mitochondrial respiratory pathway, where an excessive accumulation of lipids may be noticed in the liver. Additionally, anemia, reduction of immune function, hepatotoxicosis, hemorrhage, teratogenesis, carcinogenesis and mutagenesis are associated with aflatoxicosis [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…It also modifies lipid metabolism and the mitochondrial respiratory pathway, where an excessive accumulation of lipids may be noticed in the liver. Additionally, anemia, reduction of immune function, hepatotoxicosis, hemorrhage, teratogenesis, carcinogenesis and mutagenesis are associated with aflatoxicosis [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Village indigenous birds are constantly exposed to immunosuppressive conditions such as aflatoxicosis and infectious bursal disease virus [1]. In addition, management and ecological factors such as confinement, climatic and seasonal fluctuations, poor feeding, and worm infestations have been associated with stress and reduced immune response [2].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies found that exposure of chickens to 200 ppb aflatoxin in feed in conjunction with vaccination against Newcastle disease and two other commonly used vaccines resulted in lack of adequate protection against subsequent experimental exposure to disease [40]. The interaction of infectious bursal disease (IBD) and aflatoxicosis led to an increased mortality of 35.6% when compared to 3-21% mortality with IBD alone and 0.03% mortality with aflatoxicosis alone [41].…”
Section: Chickensmentioning
confidence: 99%